Web-based Simulations of Multi-agent Systems. (September 2017) - De Benedetti, Massimiliano; Messina, Fabrizio; Pappalardo, Giuseppe; Santoro, Corrado
This paper describes the architecture of AgentSimJs, a Javascript-based multi-agent simulator intended to execute and visualize simulations through a Web browser. It includes the needed capabilities to render a 3D scene with objects and agents. AgentSimJs has a modular architecture, the several different components provide a set of flexible primitives to program the agent behaviour. With AgentSimJs, a user can perform a fine tuning of all the aspects related to communication, motion, and group formation. Users can also define a custom network topology and communication model.